Aust J Gen Pract 2019
DOI: 10.31128/ajgp-02-19-4864
|View full text |Cite
|
Sign up to set email alerts
|

Acne in primary care: A cross-sectional analysis

Abstract: Background and objective Acne is a common chronic condition. The aim of this study was to establish the frequency and associations of consultations for acne by early-career general practitioners (general practice registrars). Methods The study was a cross-sectional analysis of data from the Registrar Clinical Encounters in Training study. Results During 2010-18, 2234 registrars contributed data for 289,594 consultations and 453,344 problems/ diagnoses. Acne comprised 0.38% (95% confidence interval [CI]: 0.36, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This makes acne the most frequent skin disease in this age group. Although more than 80% of adolescents consider acne as an unavailable part of their childhood [5], acne is associated with significant physical and psychosocial morbidity [6]. Acne can have a negative impact on patients' mood, self-esteem and quality of life (QoL) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This makes acne the most frequent skin disease in this age group. Although more than 80% of adolescents consider acne as an unavailable part of their childhood [5], acne is associated with significant physical and psychosocial morbidity [6]. Acne can have a negative impact on patients' mood, self-esteem and quality of life (QoL) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…An Australian populationbased study has previously shown acne to be a common problem in school students, with prevalence ranging from 28% in 10-12-year-olds to 93% in 16-18-year-olds [63]. While little is known about the prevalence of acne in Aboriginal youth, a cross-sectional analysis of data from primary care reported a lower frequency of acne presentations by Aboriginal youth; suggesting either a lower incidence of acne or lower rates of Aboriginal youth seeking medical care for acne [64]. Further, among Australian studies profiling the case-mix of patients seen in various dermatology outpatient clinics, presentation for acne was uncommon in Aboriginal patients [21,22,65].…”
Section: Non-infectious Skin Diseasesmentioning
confidence: 99%